Delay Early Initiation of Breastfeeding (EIBF) After Cesarean Delivery - Rizki Santy Nasution; Puput Oktamianti (Health Notions, 2023)
The cesarean delivery rate has increased globally, exceeding the standard cesarean delivery rate set by WHO. The average cesarean birth rate is 27% in 19 high-income countries with an average rate of 14 to 33% in each country. Cesarean delivery that is not based on strong medical indications has short-term and long-term health consequences. Among them is the failure of early breastfeeding initiation, which is very important for the growth and development of newborns. The purpose of this review is to see the relationship between cesarean delivery and Early Initiation of Breastfeeding (EIBF) and to see the factors that most play a role in the success of early initiation of breastfeeding after cesarean delivery. This review is based on Pubmed, Scopus, and Google Scholar data. The data is generalized and extracted into Table 1 based on factors related to the implementation of Early Breastfeeding Initiation in women with cesarean deliveries. More attention is needed on the physical, psychological and physiological recovery of lactation in women after cesarean delivery so that the interventions carried out for the success of early breastfeeding initiation can be implemented effectively. Keywords: early initiation breastfeeding; cesarean delivery